Venturiella acrifolia (Erpodiaceae, Bryophyta), new to the dry forest from Argentina - Suarez, Guillermo Martin (2023)
Background and aims: In the course of floristic dry forest sampling, specimens of Venturiella acrifolia were collected in Santiago del Estero and Santa Fe provinces. This record constitutes the first report in Argentina and the second in South America. M&M: Specimens collected in 2019 and 2023 were analyzed morphologically using conventional techniques for bryophytes and housed in DTE, LIL, MFA and SDE. Results: The species is described and illustrated. Conclusions: This work confirms the presence of Venturiella acrifolia in Argentina. The species is found in North America, Mexico, Bolivia and Argentina.